2015
DOI: 10.18203/2349-3933.ijam20150915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteoporosis using calcaneal QUS and FRAX score as a screening tool in a semi urban tertiary care hospital of South India

Abstract: The risk factors identified worldwide for development of osteoporosis are female sex, old age, small thin build or ABSTRACT Background: Osteoporosis is a silent, often found late, underdiagnosed disease characterized by low bone mass leading to increased susceptibility to fractures. With an increasingly aging population, the proportion of patients with osteopenia and osteoporosis are increasing in both developed and developing countries. The available data on osteoporosis is scanty from India. Methods: The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In low and middle-income countries, the primary barrier to osteoporosis or RO assessment is the lack of cost-effective screening tools [9]. Though Dual-energy X-ray absorptiometry (DXA) is recognized as the gold standard screening tool for osteoporosis [10], it is less accessible and less cost-feasible for low-income countries, for example, Bangladesh [11].…”
Section: Introductionmentioning
confidence: 99%
“…In low and middle-income countries, the primary barrier to osteoporosis or RO assessment is the lack of cost-effective screening tools [9]. Though Dual-energy X-ray absorptiometry (DXA) is recognized as the gold standard screening tool for osteoporosis [10], it is less accessible and less cost-feasible for low-income countries, for example, Bangladesh [11].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, studies have shown poor agreement between radial US and DXA technics and thus suggested radial QUS is not a good alternative to DXA [27,31,36]. On the other hand, QUS of calcaneus showed good correlations with DXA BMD [28,37]. This study has some limitations.…”
Section: Discussionmentioning
confidence: 60%
“…10 The present guidelines in India recommend that postmenopausal women with a prior fragility fracture may be considered for interventions without the necessity for a BMD test (other than to monitor treatment). 11 Prior to the introduction of FRAX tool, there was no universally accepted screening tool for osteoporosis in India. On the basis of a series of meta-analyses undertaken to identify clinical risk factors for osteoporosis, the Fracture Risk Assessment Tool (FRAX) was developed.…”
Section: Discussionmentioning
confidence: 99%